2017
DOI: 10.1017/s0144686x17001374
|View full text |Cite
|
Sign up to set email alerts
|

Let me grow old and senile in peace: Norwegian newspaper accounts of voice and agency with dementia

Abstract: This study analyses the remaking of dementia as a social and cultural phenomenon in the public media discourse in a welfare state Norway. A content analysis was carried out of articles on dementia published in Norwegian paper media from 1995 to 2015. The study combined the tools from quantitative corpus analyses and qualitative critical discourse analyses, making it possible to detect and interpret diachronic changes in the dementia discourse. Although the main focus in Norwegian dementia discourse has changed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…These metaphors rendered the individual merely a passive vessel within which the syndrome progresses, excluding the person from the narrative. This supports previous assertions that the voices of people with dementia tend to be notably absent from news reports of the syndrome (Van Gorp and Vercruysse, 2012; Siiner, 2019). Meanwhile, pharmaceutical interventions took on heroic significance, framed as the only possible solution to prevent dementia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These metaphors rendered the individual merely a passive vessel within which the syndrome progresses, excluding the person from the narrative. This supports previous assertions that the voices of people with dementia tend to be notably absent from news reports of the syndrome (Van Gorp and Vercruysse, 2012; Siiner, 2019). Meanwhile, pharmaceutical interventions took on heroic significance, framed as the only possible solution to prevent dementia.…”
Section: Discussionsupporting
confidence: 90%
“…Headlines such as ‘Alzheimer vaccine passes crucial test’ (Kirkman, 2006) raise expectations and hopes for an imminent cure, which is at odds with the scientific reality, while framing dementia within this biomedical discourse obscures the relevance of the social and political impact of the syndrome (Clarke, 2006). Moreover, the discourse of biomedicine prioritises the voices of scientists and clinicians at the expense of those with the condition, such that people with dementia are significantly absent in stories about dementia (Van Gorp and Vercruysse, 2012; Siiner, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…traditional media, academia), and how this knowledge is organised, produced and reproduced. Therefore, we approached discourse analysis as a method informed by social constructionism – a critical stance towards analysing how social problems, in this case, how understandings of ageing and older people are ‘constructed and presented in a broader intertextual and socio-political (con-)text’ (Siiner, 2019: 981–982).…”
Section: Methodsmentioning
confidence: 99%
“…Research on the news coverage of aging and older adults has been on the content, as well as the discursive elements, of newspaper articles (e.g., Bailey et al, 2019;Fealy et al, 2012;Koskinen et al, 2014;Marier & Revelli, 2017;Siiner, 2019). For example, through critical discourse analysis, Fealy and colleagues (2012) found that older adults were portrayed as subject to frailty, dependency, and vulnerability, effectively "othering" them (Fealy et al, 2012).…”
Section: The Portrayal Of Old Age In the News Mediamentioning
confidence: 99%